The Role of Crosslinker Content of Positively Charged NIPAM Nanogels on the In Vivo Toxicity in Zebrafish - Roberta Bilardo; Federico Traldi; Caroline H. Brennan; Marina Resmini (MDPI AG, 2023)
Polymeric nanogels as drug delivery systems offer great advantages, such as high encapsulation capacity and easily tailored formulations; however, data on biocompatibility are still limited. We synthesized N-isopropylacrylamide nanogels, with crosslinker content between 5 and 20 mol%, functionalized with different positively charged co-monomers, and investigated the in vivo toxicity in zebrafish. Our results show that the chemical structure of the basic unit impacts the toxicity profile depending on the degree of ionization and hydrogen bonding capability. When the degree of crosslinking of the polymer was altered, from 5 mol% to 20 mol%, the distribution of the positively charged monomer 2-tert-butylaminoethyl methacrylate was significantly altered, leading to higher surface charges for the more rigid nanogels (20 mol% crosslinker), which resulted in >80% survival rate (48 h, up to 0.5 mg/mL), while the more flexible polymers (5 mol% crosslinker) led to 0% survival rate (48 h, up to 0.5 mg/mL). These data show the importance of tailoring both chemical composition and rigidity of the formulation to minimize toxicity and demonstrate that using surface charge data to guide the design of nanogels for drug delivery may be insufficient.